The strengthening relationship between summer rainfall over North China and PDO since the mid-2000s - Wu, Kaijun; Liu, Haiwen; Zhao, Liang; Lin, Yihua; Yang, Zhaohong (Frontiers in Earth Science, 2022)
The interdecadal change of the summer (July-August) rainfall over North China (SRNC) is of great concern to the climate research community. Based on the sliding correlation and interdecadal difference analysis, the interdecadal change of SRNC was studied. Results shows that there was a significant wetter period of SRNC since mid-2000s, which was associated with the strengthening of negative relationship between SRNC and PDO. PDO affected the SRNC through the jet stream in the upper-level and the East Asia–Pacific (EAP) teleconnection pattern. In the negative phase of the PDO since mid-2000s, the contractive upper-level jet stream in the west of North China resulted in the abnormal updraft over southern region of North China, while the positive phase of EAP teleconnection pattern brought warm and wet southeast flow entering North China from its eastern boundary, both bringing more rainfall in North China. The abnormal water vapor transport from the western Pacific was very different from that accompanying with the East Asian summer monsoon.